Phosphorylation of Rac1 T108 by Extracellular Signal-Regulated Kinase in Response to Epidermal Growth Factor: a Novel Mechanism To Regulate Rac1 Function - Tong, Junfeng (American Society for Microbiology, 2013)
Accumulating evidence has implicated Rho GTPases, including Rac1, in many aspects of cancer development. Recent findings suggest that phosphorylation might further contribute to the tight regulation of Rho GTPases. Interestingly, sequence analysis of Rac1 shows that Rac1 T108 within the (106)PNTP(109) motif is likely an extracellular signal-regulated kinase (ERK) phosphorylation site and that Rac1 also has an ERK docking site, (183)KKRKRKCLLL(192) (D site), at the C terminus. Indeed, we show here that both transfected and endogenous Rac1 interacts with ERK and that this interaction is mediated by its D site. Green fluorescent protein (GFP)-Rac1 is threonine (T) phosphorylated in response to epidermal growth factor (EGF), and EGF-induced Rac1 threonine phosphorylation is dependent on the activation of ERK. Moreover, mutant Rac1 with the mutation of T108 to alanine (A) is not threonine phosphorylated in response to EGF. In vitro ERK kinase assay further shows that pure active ERK phosphorylates purified Rac1 but not mutant Rac1 T108A. We also show that Rac1 T108 phosphorylation decreases Rac1 activity, partially due to inhibiting its interaction with phospholipase C-γ1 (PLC-γ1). T108 phosphorylation targets Rac1 to the nucleus, which isolates Rac1 from other guanine nucleotide exchange factors (GEFs) and hinders Rac1's role in cell migration. We conclude that Rac1 T108 is phosphorylated by ERK in response to EGF, which plays an important role in regulating Rac1.